2012
DOI: 10.4103/0975-1475.109895
|View full text |Cite
|
Sign up to set email alerts
|

A cephalometric study of skulls from the Bahriyah oasis

Abstract: Objectives:To determine the craniofacial characteristics of crania from the Bahariyah oasis dating from the Greco-Roman period and to compare their cephalometric traits with other ancient Egyptian samples from various time periods and to evaluate sexual dimorphism.Materials and Methods:The sample comprised 149 skulls (90 males and 59 females), belonging to the Greco-Roman (332 B.C. – 395 A.D.). Lateral and postero-anterior cephalograms were taken. Sixteen linear measurements were analyzed and six indices were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…It is suggested, regarding the small difference between men and women in those two measures (left and right sides), that this could be justified by the large intermingling existent in Brazil, which would have caused modifications in the characteristics that would be distinguishable among the different ethnicities, therefore allowing for less sexual differentiation. Such situation was also found by Steyn & Iscan [13], in which they verified that the bizygomatic measure was the most dimorphic among the 91 evaluated skeletons from the Pretoria and Witwatersand Collection.…”
Section: Discussionsupporting
confidence: 71%
“…It is suggested, regarding the small difference between men and women in those two measures (left and right sides), that this could be justified by the large intermingling existent in Brazil, which would have caused modifications in the characteristics that would be distinguishable among the different ethnicities, therefore allowing for less sexual differentiation. Such situation was also found by Steyn & Iscan [13], in which they verified that the bizygomatic measure was the most dimorphic among the 91 evaluated skeletons from the Pretoria and Witwatersand Collection.…”
Section: Discussionsupporting
confidence: 71%
“…The researchers used cephalometric analysis according to Sassouni. It was found that the representatives who lived in this region have sharp differences with other morphotypes found in modern Egypt [29].…”
Section: Indexes Young Men S-n-a S-n-pog S-n-b A-n-pogmentioning
confidence: 76%
“…Measurements of five skulls with noted ACD were analyzed to quantify osteological traits, assess intragroup relationships (variance of structures), and determine type of intentional cephalic modeling (Brewster et al, 2014; Dudzik & Kolatorowicz, 2016; Zaki et al, 2012). Thirteen landmarks homologous to traditional craniometric points that cover the main components of the skull (facial region, neurocranium, and base) were used (Langley et al, 2016; Romano‐Pacheco, 1965; Romano‐Pacheco, 2005; Serrano‐Sánchez et al, 2021).…”
Section: Methodsmentioning
confidence: 99%